Некоторые моменты сопоставительного анализа фонетики русского и туркменского языков - Іванова, Т.А.; Винниченко, С.Д.; Атаєв, А.; Иванова, Т.А.; Винниченко, С.Д.; Атаев, A.; Ivanova, T.A.; Vinnichenko, S.D. (Харківський національний університет імені В.Н. Каразіна, Центр міжнародної освіти, 2009)
В статье дается сопоставление некоторых аспектов фонетического строя русского и туркменского языков.
Some Aspects of the Comparison Analysis of Russian and Turkmen Phonetics
ДЕЯКІ МОМЕНТИ ПОРІВНЯЛЬНОГО АНАЛІЗУ ФОНЕТИКИ РОСІЙСЬКОЇ ТА ТУРКМЕНСЬКОЇ МОВ
The comparison of some phonetic aspects of Russian and Turkmen languages has been given in this article.
Keywords: pronunciation; phoneme; grapheme; фонема; графема; вимова; фонема; графема